Empty Bullet-Related Ocular Injuries During Military Shooting Training: A 20-Year Review. Issue 5 (6th December 2019) - Guven, Soner; Durukan, Ali Hakan
Abstract: Introduction: Empty bullet-related ocular injuries (EBOI) are rare and may result in unfavorable visual outcomes due to both open globe and closed globe injuries. To our knowledge, no reports of such injuries in terms of outcomes have been previously described in the literature. The aim of this study was to describe the treatment performed and ocular outcomes of such injuries. Materials and Methods: EBOI of 23 cases were reviewed who were referred to Gulhane School of Medicine Department of Ophthalmology between January 1998 and January 2018. Patient demographics, ocular signs (initial and final), injury types, type and number of interventions, and ocular trauma scores were recorded. Results: In total, 23 eyes of the 23 patients with an average age of 22.3 ± 4.54 years (range, 20–41 years) were included in the study. All of the patients were male, and all injuries were due to empty bullets during shooting training. None had ocular protection at the time of ocular injury. Fourteen patients (60.9%) were open globe injuries, whereas nine (39.1%) of them were closed globe injuries. Mean ocular trauma scores category of the cases was 2.52 ± 1.03. The baseline and final visual acuity was 20/200 or better in 21.7% and 69.5% of eyes, respectively. Nineteen eyes (82.7%) had undergone a total of 31 surgeries with a 1.34 ± 0.88 surgery average. Conclusions: The prognosis of EBOI is unpredictable and is dependent on the severity of ocular damage. The best treatment option is prevention of EBOI with protective eyewear.